The effects of perceived justice in service recovery on firm reputation and repurchase intention in airline industry - Nikbin, Davoud; Jalalkamali, Mohammad; Heydari, Alireza; Armesh, Hamed (Academic Journals, 2011)
The purpose of this study is to assess the influence of perceived justice on repurchase intention and to examine the moderating role of firm reputation in the relationship between perceived justice and repurchase intention. Data were gathered by means of survey from airline passengers who experienced a service failure and subsequently a service recovery within past one year. The results show the effect of distributive justice on repurchase intention was stronger than procedural and interactional justice. Additionally, hierarchical regression analyses suggested that firm reputation plays a moderating role between perceived justice and repurchase intention in the distributive and interactional justice dimensions. Although, prior research has developed an understanding of the role of firm reputation on behavioral intentions, however, this study additionally examined the role of firm reputation as the moderator in this relationship. Managerial implications of these findings are briefly discussed.